Preparation and Characterization of Rivastigmine Transdermal Patch Based on Chitosan Microparticles - Sadeghi, Mohsen (Iran J Pharm Res, 2016)
Here we report a novel approach for preparation of a 6-day transdermal drug delivery system (TDDS) as treatment for mild to moderate Alzheimer’s disease. The spray drying method was used to prepare microparticles containing the anti-Alzheimer drug, Rivastigmine, in combination with the natural polymer, chitosan, for transdermal drug delivery applications. The content of the drug was determined by High Performance Liquid Chromatography (HPLC) method which was validated as per FDA guidelines. The morphology and size range of the microparticles were determined; and the effect of drug concentration in the solution injected into the spray dryer on the particles characterizations was studied. The stability of Rivastigmine at high temperature was confirmed using FTIR analysis as well as a validate HPLC assay. The obtained results show that the drug was stable at high temperatures with 7 to 42% loading in the microparticles, and the higher drug concentrations of the solution injected into the spray dryer resulted in increase of the drug loading, surface drug and microparticles distortion. The TDDS containing the microparticles was also prepared with microparticle to dry adhesive ratios of 5, 10 and 15% using acrylic adhesive. Based on adhesion properties of the patches, gained from the probe tack and the peel adhesion 180° tests, and the 15% patch by having more drug content per unit area of the patch, and still having similar adhesion properties was compared to the microparticles-free patch of 5.1% Rivastigmine salt (equivalent to the drug content of the 15% patch) from the permeation point of view by using Franz cell diffusion over 6 days. The drug permeation rate from the microparticle-free patch was slower than the 15% microparticles patch, which is the result of crystallization of Rivastigmine salt in the acrylic adhesive. The 6-day-prepared TDDS can be considered as an alternative for one-week application of 6 Exelon patches.